Implications and Competitiveness of Regions on Regional Development of Central Java - Soebagiyo, Daryono (Universitas Muhammdaiyah Surakarta, 2014)
Regional Competitiveness be one of the issues in regional development policy since the enactment of regional autonomy. Based on the results of the efficiency analysis found 11 areas of the city and district have the efficiency and 4 districts do not have the efficiency. Regional Competitiveness in Central Java based Comparative Advantage and Competitive known regions that have a high comparative and competitive advantages consist of 4 areas. Regional Mapping Based on Efficiency and Productivity Local known areas that have high efficiency and productivity which consists of 4 areas. Based Competitive Advantage Regional Productivity is high and not found. Under the Regional Competitiveness and Regional Productivity high was not found. Based on Comparative Advantage and Regional Development area there are 4 high. Based Competitive Advantage and Regional Development of high there are 2 areas. Based on Regional Productivity and Regional Development of high there are 2 counties and cities